Hydroxylated Dimeric Naphthoquinones Increase the Generation of Reactive Oxygen Species, Induce Apoptosis of Acute Myeloid Leukemia Cells and Are Not Substrates of the Multidrug Resistance Proteins ABCB1 and ABCG2 - Rena G. Lapidus; Brandon A. Carter-Cooper; Mariola Sadowska; Eun Yong Choi; Omasiri Wonodi; Nidal Muvarak; Karthika Natarajan; Lakshmi S. Pidugu; Anil Jaiswal; Eric A. Toth; Feyruz V. Rassool; Arash Etemadi; et al. (MDPI AG, 2016)
Selective targeting of the oxidative state, which is a tightly balanced fundamental cellular property, is an attractive strategy for developing novel anti-leukemic chemotherapeutics with potential applications in the treatment of acute myeloid leukemia (AML), a molecularly heterogeneous disease. Dimeric naphthoquinones (BiQs) with the ability to undergo redox cycling and to generate reactive oxygen species (ROS) in cancer cells are a novel class of compounds with unique characteristics that make them excellent candidates to be tested against AML cells. We evaluated the effect of two BiQ analogues and one monomeric naphthoquinone in AML cell lines and primary cells from patients. All compounds possess one halogen and one hydroxyl group on the quinone cores. Dimeric, but not monomeric, naphthoquinones demonstrated significant anti-AML activity in the cell lines and primary cells from patients with favorable therapeutic index compared to normal hematopoietic cells. BiQ-1 effectively inhibited clonogenicity and induced apoptosis as measured by Western blotting and Annexin V staining and mitochondrial membrane depolarization by flow cytometry. BiQ-1 significantly enhances intracellular ROS levels in AML cells and upregulates expression of key anti-oxidant protein, Nrf2. Notably, systemic exposure to BiQ-1 was well tolerated in mice. In conclusion, we propose that BiQ-induced therapeutic augmentation of ROS in AML cells with dysregulation of antioxidants kill leukemic cells while normal cells remain relatively intact. Further studies are warranted to better understand this class of potential chemotherapeutics.